Profiling of Metabolites in Organically Grown Plums from Norway: Does Location or Cultivar Matter? - Mekjell Meland; Dragana Dabić Zagorac; Mihajlo Jakanovski; Milica Sredojević; Maja Natić; Marko Kitanović; Milica Fotirić Akšić (MDPI AG, 2024)
The aim of this work was to investigate the influence of two locations and seven cultivars on the profiling of metabolites in organically grown plums (Prunus domestica L.) fruit in Norway. P, K, and Ca were most abundant in the studied fruits, while Ba and Sr formed a clear line between the locations. The most abundant sugars were glucose, fructose, sucrose, and sorbitol, which together accounted for up to 97.00%. Quinic acid and malic acid were the predominant organic acids, while chlorogenic acid, rutin, and kaempferol-3-O-glucoside were the most abundant polyphenols. Plums from Ullensvang were characterized by a higher content of minerals, sugars, organic acids, total polyphenol content (TPC), and radical scavenging activity (RSA), while plums from Telemark had a higher content of quantified polyphenols. The cultivar 'Mallard' had the highest mineral and radical scavenging activity, 'Opal' had the sweetest fruit, 'Jubileum' had the highest acidity, 'Excalibur' had the highest TPC content, and 'Valor' stored the highest content of quantified polyphenols, especially chlorogenic acid. These results provide comprehensive information on the chemical profiles of selected plum cultivars, suggesting that organic plums are a rich source of beneficial compounds that can have a positive impact on human health.